I need help with this equation and need help checking my work.. -2 (b+5) = -6

Thank you for the opportunity to help you with your question! Hope your day is going well!

The goal is to get the b by itself.

first step: distribute the -2

-2(b+5)=-6

-2b-10=-6

Step 2: add 10 to both sides

-2b=4

Step 3: divide -2 to both sides

b=-2

To make sure your answer is right, substitute -2 into the original equation

-2(-2+5)

-2(3)=-6

Which is the answer!

thank you very much for helping me... :)

wait I just need to ask... how did you get three when you checked shouldn't it be -4?

5-2=3

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up